Simulation and utilization of irradiation facilities - Crouch, Bradley (My University, 2025)
Simulations were created and utilized for different irradiation facilities to examine the effects that neutron and x-ray radiation has on Caco-2 and HepG2 cell cultures. Once outside Earth’s geomagnetic field, the radiation environment becomes more harsh, causing there to be greater risk to the astronauts. One of the major risks of interplanetary space travel is space radiation-induced carcinogenesis. With increased duration of the mission, the risk to the astronauts increases. This increased risk of carcinogenesis causes the maximum duration of a mission to be limited. The radiation field that impinges upon the astronauts is complex and is made up of a variety of radiation types. The complex field of space radiation needs a terrestrial experimental source for comparative studies. The radiation that was primarily examined in this work was neutron and x-rays. The neutron sources that were simulated are the KSU TRIGA Mark II Thermal Column and deuterium-tritium fusion neutrons. The x-ray sources were a 6 MV Varian LINAC and a RadSource RS1800 biological irradiator. Accurate understanding of the dose to astronauts is vital to astronaut safety and the success of the mission, which leads to the need for accurate models and simulation. The nuclear reactor model, which was partially modeled in a previous work, was upgraded to include the thermal column. An MCNP FMESH4 tally was used to determine the simulated neutron flux across the irradiation section of the thermal column. The output was converted to neutrons per kilowatt using the k_ef f and nubar. The neutron generator experiment room was modeled in previous work. The neutron generator had to be moved as the previous simulation had the source placed in a different location and the cell cultures were modeled. The cell culture dishes were modeled and located inside of the experiment room where they would be placed in a physical experiment. The MCNP F6 energy deposition tally was used to determine the dose rate from the neutron generators on the cells. The RS1800 was previously modeled, but the source term needed to be changed to account for the different voltage and current settings used for the experiments. The voltage and current control the x-ray spectrum; in the original model the settings were 130 kV and 1 mA for the voltage and current, respectively. For this work, the voltage was increased to 160 kV and either 1 mA or 12.5 mA were used for the current depending on if the irradiation was chronic or acute. An MCNP F4 tally was used with a energy-dependent response function to convert the flux density into dose rate. Experiments were conducted to examine the effects induced in the cells by different types of radiation. The doses to the cells that were irradiated were accurately characterized for x-ray and neutrons. The neutrons came from a deuterium-tritium fusion neutron generator with energies of 14.1 MeV and a dose rate of approximately 60 mGy h⁻¹. The x-rays came from a RS1800 biological irradiator and a 6 MV LINAC; the dose rates of these machines varied and are discussed in the section with each experiment. In the neutron experiments, the dose rate was originally incorrectly found to be 5 mGy h⁻¹. The target dose in the neutron experiments was 40-80 mGy, which would have taken 48-106 min rather than the 8-16 hours used in the experiment. The increased dose to the cells led to high cell death and very little usable data after the experiment. The x-ray doses ranged from 0.5 Gy up to 16 Gy in some experiments. Multiple cell assays were used in the quantification of the radiation damage including cell viability, reactive oxygen species (ROS), and double-strand break (DSB). Cell viability assays examine the survivability of cells post exposure. ROS assays examine the reactive oxygen species created by the cell in response to the radiation. The DSB assay stain the double-strand breaks caused by damage to the DNA making them quantifiable. The assays all utilize immunostaining to generate the fluorescence that is seen in the confocal images. These images were analyzed to get the data. After irradiation of the cells and the different cell assays were performed, there was a dose dependent response in the cell death using a live/dead assay. There was no change seen in the cell viability using a MTT assay because of the cell density. There was little to no ROS generated in any of the experiments, since Caco-2 and HepG2 are epithelial cell lines. There was a dose dependent response to the DSB generated after x-ray exposure to acute exposure. There were significantly fewer DSB generated after chronic exposure to x-rays, as expected, due to the smaller dose received at one time. In between fractions, the 24 hours of repair time allows for the cell to repair some of the DSBs.
Keywords: Simulation; MCNP; Caco-2; HepG2; Neutron; X-ray